CD22: A Regulator of Innate and Adaptive B Cell Responses and Autoimmunity - Clark, Edward A.; Giltiay, Natalia V. (Frontiers in Immunology, 2018)
CD22 (Siglec 2) is a receptor predominantly restricted to B cells. It was initially characterized over 30 years ago and named ‘CD22’ in 1984 at the 2nd International workshop in Boston [1]. Several excellent reviews have detailed CD22 functions, CD22-regulated signaling pathways and B cell subsets regulated by CD22 or Siglec G [2; 3; 4]. This review is an attempt to highlight recent and possibly forgotten findings. We also describe the role of CD22 in autoimmunity and the great potential for CD22-based immunotherapeutics for the treatment of autoimmune diseases such as systemic lupus erythematosus (SLE).